Edukasi Dan Penilaian Kadar Albumin Pada Kelompok Lanjut Usia Dalam Pencegahan Sarkopenia - Frisca Frisca; Santoso, Alexander Halim; Warsito, Jonathan Hadi; Syarifah, Andini Ghina; Gunaidi, Farell Christian; Destra, Edwin; Firmansyah, Yohanes (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2024)
Sarcopenia is a medical condition characterized by a progressive decrease in skeletal muscle mass as well as muscle strength. Sarcopenia in the elderly causes an increased risk of falls, fractures and mortality. The main risk factors include advanced age, lack of physical activity, malnutrition, and chronic disease. Deficiency of albumin, a protein important for maintaining osmotic pressure and nutritional status, is often associated with malnutrition and sarkopenia. This community service activity was attended by 93 elderly people with an average age of 74 years. The results showed that the majority of participants had normal albumin levels, but there was a significant proportion who experienced hypoalbuminemia, more commonly found in men than women. Education and screening are carried out to increase awareness regarding the importance of albumin intake in preventing sarkopenia. A holistic and integrated nutritional approach is needed in the management of sarcopenia. Appropriate nutritional interventions, including increasing protein intake from foods such as snakehead fish, can increase serum albumin levels and prevent muscle mass loss. Collaboration between nutritionists, physicians, and other health professionals is essential to designing and implementing a comprehensive treatment plan. It is hoped that with appropriate monitoring and treatment, the quality of life of elderly people with sarkopenia can be improved. Keywords: albumin, education, hypoalbuminemia, elderly, sarcopenia